An Analysis of Students’ Speaking Ability of The Second Grade MAN 1 POLMAN; An Overview of Covid-19 Adapted Learning - Ratna Sari; Muhammad Danial; Sukmawati Yasim (Polewali: Dewan Pengurus Daerah Sulawesi Barat Forum Dosen Indonesia, 2021)
The purpose of this study was to analyze the speaking ability of class XI EXACT MAN 1 POLMAN students in the 2020 academic year. This research is a descriptive qualitative research. Data collection techniques used speaking tests and questionnaires. Researchers took 10 students as research subjects. The results showed that the students were able to speak English well in terms of fluency and pronunciation. As for the results of the student perception questionnaire, the researcher found that vocabulary is one of the problems experienced by students when they want to speak English and have difficulty pronouncing words correctly so they are afraid of being wrong. And sometimes it's difficult to make sentences correctly.